2006
DOI: 10.1002/ejoc.200600517
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Nonbonding Interactions between Selenium and Sulfur – Spectroscopic Evidence and Importance in Asymmetric Synthesis

Abstract: Keywords: Asymmetric electrophilic additions / Chiral selenenylating reagents / Noncovalent interactions / Selenium / Sulfur Chiral sulfur-containing electrophilic selenium reagents can be employed to effect efficient asymmetric syntheses. Spectroscopic and chemical evidence demonstrate that the observed high selectivity of the asymmetric reactions is associ-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 41 publications
1
30
0
1
Order By: Relevance
“…It was found that the 77 Se NMR chemical shift (δ Se ) is sensitive to the environment around the Se center, and its shift can be used as a measure of the strength of the nonbonding interactions of Se with other atoms with lone pairs. [24][25][26] To explore whether there are intramolecular nonbonding interactions between the Se centers of 1-3 in solution, first we compared the 77 Se NMR chemical shifts of 1 with the model compounds 12-16 shown in Figure 5. Originally we thought that methyl phenyl selenide (16) (δ Se = 199 ppm) [26] might be a good model for 1.…”
Section: Nmr Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the 77 Se NMR chemical shift (δ Se ) is sensitive to the environment around the Se center, and its shift can be used as a measure of the strength of the nonbonding interactions of Se with other atoms with lone pairs. [24][25][26] To explore whether there are intramolecular nonbonding interactions between the Se centers of 1-3 in solution, first we compared the 77 Se NMR chemical shifts of 1 with the model compounds 12-16 shown in Figure 5. Originally we thought that methyl phenyl selenide (16) (δ Se = 199 ppm) [26] might be a good model for 1.…”
Section: Nmr Investigationsmentioning
confidence: 99%
“…[24][25][26] To explore whether there are intramolecular nonbonding interactions between the Se centers of 1-3 in solution, first we compared the 77 Se NMR chemical shifts of 1 with the model compounds 12-16 shown in Figure 5. Originally we thought that methyl phenyl selenide (16) (δ Se = 199 ppm) [26] might be a good model for 1. However, comparison of its δ Se value with that obtained for 12 shows that the latter is better suited for our purpose.…”
Section: Nmr Investigationsmentioning
confidence: 99%
“…A similar 1,4 short contact between S and Se atoms has been characterized in the structure of 2 with SÁÁÁSe distance of 3.199 Å (Boryczka et al, 2001). The nonbonding selenium-sulfur interaction and its importance in asymmetric synthesis were observed in arylselenenyl halides (Tiecco et al, 2006).…”
Section: -Bmentioning
confidence: 68%
“…The title compound represents the first monomeric organoselenenyl chloride stabilized intramolecularly by an interaction of this type. Previously, the analogous stabilization of monomeric organoselenenyl chlorides by intramolecular secondary SeÁ Á ÁS (Tiecco et al, 2006) and SeÁ Á ÁN (Panda et al, 1999;Klapö tke et al, 2004;Kulcsar et al, 2007;Pö llnitz et al, 2011) interactions have been reported.…”
Section: Structural Commentarymentioning
confidence: 95%